Effect of Sowing Date on Germination and Vigour of Soybean (Glycine max (L.) Merr) Seeds (The Agriculturists, 2013)
An experiment was carried out at the Agronomy Field Laboratory of Bangladesh Agricultural University, Mymensingh during three consecutive seasons in 2004-2006 to find out the effect of sowing date on physiological quality of soybean seed. The experiments included six sowing dates viz. 4 Nov, 24 Nov, 14 Dec, 3 Jan, 23 Jan and 12 Feb and two cultivars namely G-2 and PB-1 in Rabi 2004-05; four sowing dates viz. 25 Jul, 14 Aug, 3 Sept and 23 Sept and three cultivars namely G-2, PB-1 and BS-5 in Kharif II 2005; four sowing dates viz. 26 Nov, 16 Dec, 5 Jan, and 25 Jan, and two cultivars viz. G-2 and PB-1 in Rabi 2005-06. The experiments were conducted in split-plot design with three replications. Results revealed that cultivar G-2 had higher germination and vigour than cultivar PB-1 or BS-5 in all the three seasons. November and December sowing produced seeds with higher germination and vigour for all the cultivars in Rabi season. On the other hand, September sowing produced seeds with high germination and vigour during Kharif II. The study indicated that soybean seeds with high germination and vigour could be obtained by sowing during November to December in Rabi season and August to September in Kharif-II season. DOI: http://dx.doi.org/10.3329/agric.v11i1.15245 The Agriculturists 2013; 11(1) 67-75